The role of agro-clusters in the agricultural sector of the country in the digital economy - Yuldashova Nilufar Ziyabaevna (Genius Publishing Group, 2021)
This article describes the development and importance of agro-clusters in the agricultural sector in the context of the developing digital economy in our country, the advantages of clusters in agriculture, as well as signs of improving the organizational and economic mechanisms of the service sector.
Keywords: Digital economy; cluster; agriculture; advantages of agroclusters